Evolution and Dynamics of Technology Based Accounting Information: A Bibliometric Study - Fanggidae, Herny Constantia; Ala, Helda Marlin (Westscience Press, 2024)
This bibliometric study delves into the evolution and dynamics of technology-based accounting information systems (AIS), exploring the intersection of technological advancements and accounting practices. The integration of technology in accounting has catalyzed significant transformations, reshaping how financial data is managed, analyzed, and reported. Through a comprehensive analysis of 780 publications spanning from 1977 to 2024, this research uncovers key trends, influential works, and emerging themes in the field of technology-based AIS. Utilizing bibliometric techniques such as co-citation analysis and network visualization, the study provides insights into the collaborative landscape, thematic clusters, and temporal trends within the domain of technology-based AIS research. The findings shed light on the evolution of AIS research, highlighting the increasing relevance of emerging technologies such as artificial intelligence and blockchain, while also identifying potential areas for future investigation.